Exploring the use, outcomes, barriers, and facilitators of prehabilitation and rehabilitation in abdominoplasty surgeries: A scoping review - Gasparini L.H.M.* (2024)
© 2024 British Association of Plastic, Reconstructive and Aesthetic SurgeonsObjective: This review aimed to map the literature on prehabilitation and rehabilitation in adults undergoing abdominoplasty, identifying gaps and areas for future research. Methods: The review followed the PRISMA guidelines for Scoping Reviews and was registered on the Open Science Framework platform (https://osf.io/m4k5s). The search for studies was conducted in the following electronic databases: PubMed, Scopus, EMBASE, Web of Science, PEDro, LILACS, The Cochrane Library, and CINAHL. The search strategy used the PCC approach: P: abdominoplasty surgery; C: prehabilitation or rehabilitation interventions; C: patient-related outcomes, hospital outcomes, safety outcomes, mortality, intervention description, feasibility of intervention selection and delivery, reported barriers and facilitators, and various study designs. Results: Among the 2444 references examined, 12 studies met the inclusion criteria, predominantly consisting of small clinical trials. The most frequent surgical approach was combined abdominoplasty, present in 58.3% of the studies. Physiotherapists integrated with the prehabilitation and/or rehabilitation team in 33.3% of cases. Notably, 75% of the studies focused on postoperative rehabilitation, with lymphatic drainage techniques being the most common intervention, appearing in 41.7% of the studies. 33.3% of the studies mentioned respiratory complications such as atelectasis, pneumonia, and respiratory failure as postoperative occurrences. Some gaps were identified, including insufficiently detailed reports of interventions and diversity in the type and timing of outcome measurements. Conclusions: This review highlights the lack of data on the effects of prehabilitation and rehabilitation in patients undergoing abdominoplasty, due to the diversity of measures and variable assessment times, emphasizing the need for standardization and multicenter studies to determine optimal interventions and their impacts.